The Human Mixed Lineage Leukemia 5 (MLL5), a Sequentially and Structurally Divergent SET Domain-Containing Protein with No Intrinsic Catalytic Activity. - Sarah Mas-Y-Mas; Marta Barbon; Catherine Teyssier; Hélène Déméné; João E Carvalho; Louise E Bird; Andrey Lebedev; Juliana Fattori; Michael Schubert; Christian Dumas; William Bourguet; Albane le Maire (PLoS ONE)
Mixed Lineage Leukemia 5 (MLL5) plays a key role in hematopoiesis, spermatogenesis and cell cycle progression. Chromatin binding is ensured by its plant homeodomain (PHD) through a direct interaction with the N-terminus of histone H3 (H3). In addition, MLL5 contains a Su(var)3-9, Enhancer of zeste, Trithorax (SET) domain, a protein module that usually displays histone lysine methyltransferase activity. We report here the crystal structure of the unliganded SET domain of human MLL5 at 2.1 Å resolution. Although it shows most of the canonical features of other SET domains, both the lack of key residues and the presence in the SET-I subdomain of an unusually large loop preclude the interaction of MLL5 SET with its cofactor and substrate. Accordingly, we show that MLL5 is devoid of any in vitro methyltransferase activity on full-length histones and histone H3 peptides. Hence, the three dimensional structure of MLL5 SET domain unveils the structural basis for its lack of methyltransferase activity and suggests a new regulatory mechanism.